Optimization of discrete frequency coding waveform for MIMO radar using Modified Ant Colony Optimization algorithm - Reddy, B. Roja; Uttarakumari, M. (2014 First International Conference on Networks & Soft Computing (ICNSC2014), 2014)
In this paper, Modified Ant Colony Optimization (M_ACO) algorithm is proposed to optimize the modified Discrete Frequency Coding Waveform (DFCW) sequence sets in lesser computation time. The sequence sets are optimized to generate orthogonal DFCW code sets. M_ACO algorithm is the combination of Ant Colony Optimization (ACO) and Hamming Scan algorithm. This algorithm is a graph based approach to find the best optimized sequence. The simulation of the orthogonally optimized modified DFCW code set sequences generated using M_ACO shows better results than other optimization algorithms known in the literature. The orthogonally optimized modified DFCW code set sequences are promising for practical application to netted radar and MIMO radar systems.